A SIMILAR OBJECTIVE PISA INTERNATIONAL STUDENT ASSESSMENT PROGRAM TO DEVELOP STUDENT LITERACY IN PHYSICS TEACHING - Меликузиев Дадакузи Джуракузиевич (Galaxy International Interdisciplinary Research Journal, 2022)
The article sets out the task of forming natural science literacy in students of the 8th grade on the basis of performing tasks similar to PISA tasks in physics lessons. An example of a task that meets the didactic requirements is given.